2012
DOI: 10.3349/ymj.2012.53.2.386
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Relationship between Color Doppler Ultrasonography Findings and the Number of Internal Spermatic Veins in Varicoceles

Abstract: PurposeThe improvement of testicular volume, testosterone levels and sperm concentration was suggested to be significantly associated with the number of internal spermatic veins (ISVs) ligated during varicocelectomy. Herein, we investigated preoperative color Doppler ultrasonography (CDU) findings as potential preoperative predictors of the number of ISVs requiring ligation during microsurgical subinguinal varicocelectomy.Materials and MethodsIn a prospective evaluation of 40 patients, maximal vein size and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…35 cm in the right spermatic vein in the case of insufficient valves resulting in a hydrostatic pressure on the left of over 30 mmHg and on the right of more than 27 mmHg on the distal pampiniform plexus. Kim et al concluded that both the height of the blood column and the number and cross-sectional area of the branches of the pampiniform plexus are responsible for the increased pressures [12]. This results, as explained by the Bernoulli equation, in increased static pressure in the pampiniform plexus with simultaneously slower flow rates, with the pressure increasing as the number of branches and thus the cross-sectional area of the pampiniform plexus increase.…”
mentioning
confidence: 99%
“…35 cm in the right spermatic vein in the case of insufficient valves resulting in a hydrostatic pressure on the left of over 30 mmHg and on the right of more than 27 mmHg on the distal pampiniform plexus. Kim et al concluded that both the height of the blood column and the number and cross-sectional area of the branches of the pampiniform plexus are responsible for the increased pressures [12]. This results, as explained by the Bernoulli equation, in increased static pressure in the pampiniform plexus with simultaneously slower flow rates, with the pressure increasing as the number of branches and thus the cross-sectional area of the pampiniform plexus increase.…”
mentioning
confidence: 99%
“…The number of spermatic veins ligated intraoperatively was correlated with pre-operative ultrasound findings. Maximal reflux velocity and total cross-sectional area of the affected testicular veins on ultrasound were found to accurately relate with the number of veins ligated during surgery (Kim et al, 2012). Regardless of whether such a relationship carries a diagnostic value, its clinical relevance is probably more important for the clinician.…”
Section: Discussionmentioning
confidence: 96%
“…However, the greatest improvement was seen in men with grade II rather than grade III varicocele. They suggested that the definite relationship still needs to be clarified ( 24 ). Although conflicting results are present, it is still considered that individual sperm parameter is not diagnostic for infertility, as a normal count of motility may not result in a higher chance of pregnancy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shindel et al reported that grade II varicocele benefited the most regarding sperm morphology, where marked improvements were observed one year after varicocelectomy. However, the number of the ligated vein was not predictive of this improvement ( 24 ). Majzoub et al also reported no significant change in sperm volume obtained from the pre and postoperative semen analysis, regardless of the number of ligated veins ( 9 ).…”
Section: Discussionmentioning
confidence: 99%